Analisis Resiko Penangkar Benih Padi Pada Program Desa Mandiri Benih Di Kabupaten Pringsewu - dyah rianita Susanti (Journal of Food System & Agribusiness, 2017)
ABSTRACTÂ The objective of this research was to analyze the risk of rice seed breeder in Pringsewu District. The research was conducted in Pringsewu District. The location was determined purposively, considering that Pringsewu Regency was a rice producing center in Lampung Province. Based on the calculation, the study sample consisted of 37 rice breeders and 37 non-breeders. The data collection of this research was conducted in November 2017. This research employed variation coefficient method to analyze risk. The coefficient of variation (CV) is a measure of the relative risk obtained by dividing the standard deviation by the expected value. The results of the research showed that the level of risk of rice farming in Pringsewu regency for non-paddy breeder farmers was higher than paddy farmer breeders.Â Â